O tempo do olhar de Patricio Guzmán: as representações da história no filme Salvador Allende - Monteiro, Fábio (2016)
Salvador Allende is a documentary released in 2003 by Patricio Guzmán. It is proposed as a biopic of personal life and political career of former Chilean democratically elected president in September 1970 by a multi-party composition of the left, the Unidade Popular. In defense of a legal and democratic path to socialism, the Allende government achieved successes both in political and economic area, but at the same time had to face the decisive intervention of the right sectors that relied on massive Unite States investment in overthrowing their government. Salvador Allende was the founder and leader of the Chilean Socialist Party and won the presidential election after three successive election campaigns. Its government base, the Unidade Popular, was composed by sector representatives not only of the Socialist Party, but also communists, center-left sectors and sectors of the radical left. This plural political arrangement was a decisive factor in defining the direction of the Government Allende crisis. After the visit of Fidel Castro in December 1971, the reactionary sectors have adopted media strategies and tactics increasingly decisive policies that culminated in the military coup of September 11, 1973. The release of the film Salvador Allende took the events around the thirty years of the military coup to reconstruct this history. Taking into account that every movie involves choices as the definition of interviews, certain sound interventions, songs and archival footage and different narrative strategies, this thesis collates historical arguments brought by the film with a consolidated bibliography on the subject